GRAMMATICAL PERSPECTIVES OF THE TEACHER-STUDENT DIRECTIVES AS THE INSTRUCTION TO HIGH SCHOOL LEARNERS IN MULTILINGUAL CONTEXTS: A STUDY CASE - V. Rido Rasmodjo (Universitas Negeri Padang, 2016)
Directives, apart from declaratives and interrogatives, are forms of teacher – student interactions which are important in second language learning. Forms of directives the classroom teachers apply during the classroom interactions, especially in high schools, determine the colors of the teaching-learning activities conducted in classroom. This study intends to figure out the nature of directives used by novice teachers during their teaching practice teaching in high schools in Jakarta. The types of directives the novice teachers apply will be analyzed using the grammatical perspectives. Drawing from the theory on the types and functions of directives proposed by Holmes (1983) and Mauri and Sauza (2012), this study will also try to find out whether certain types of directives are more preferable than the others and how the novice teachers utilize the types in creating the more conducive learning environment. The discussion of the types as well as the functions of directives will hopefully give a richer insight into the possible directives the novice teachers may apply in their classes. The proper choice of the directives used will eventually play an important role in the success of the practicum as well as the second language teaching.